The Effect of Gender and Gender Pairing on Bargaining: Evidence from an Artefactual Field Experiment - Ben D'Exelle; Christine Gutekunst; Arno Riedl (Institute of Labor Economics (IZA), 2020)
Men and women negotiate differently, which might create gender inequality in access to resources as well as efficiency losses due to disagreement. We study the role of gender and gender pairing in bilateral bargaining, using a lab-in-the-field experiment in which pairs of participants bargain over the division of a fixed amount of resources. We vary the gender composition of the bargaining pairs as well as the disclosure of the participants' identities. We find gender differences in earnings, agreement and demands, but only when the identities are disclosed. Women in same-gender pairs obtain higher earnings than men and women in mixed-gender pairs. This is the result of the lower likelihood of disagreement among women-only pairs. Women leave more on the bargaining table, conditional on their beliefs, which contributes to the lower disagreement and higher earnings among women-only pairs.
Keywords: C9; J16; O12; 330; bargaining; gender; gender pairing; beliefs; experiment